Pengembangan Media Pembelajaran Bangun Datar Menggunakan Permainan Engklek untuk Siswa Kelas II SD/MI - Diyah Andini Kusumastuti; Umi Mahmudah (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This research aims to develop and evaluate learning media based on traditional engklek games in improving the understanding of the concept of flat building in grade II students of SD/MI. The background of the research is based on the low interest and understanding of students in basic geometry materials and the lack of contextual and fun learning media innovations. The research approach used is qualitative descriptive with data collection techniques through observation, interviews, and documentation. The results showed that the ankle media was effective in improving students' understanding of flat shapes such as squares, triangles, and circles, with an increase in the average student score from 66.2 to 83.5. In addition, the use of this media also increases students' enthusiasm, active participation, and collaboration and socialization skills during the learning process. These findings are in line with constructivist and sociocultural theories that emphasize the importance of active and contextual learning. Engklek learning media not only enriches a meaningful mathematics learning experience, but also contributes to the preservation of local culture. This study recommends the use of traditional games as an innovative strategy in mathematics learning in elementary schools.